EVALUASI PROGRAM KELUARGA HARAPAN (PKH) DI DESA WINDUAJI KECAMATAN PAGUYANGAN KABUPATEN BREBES - Denok Kurniasih; Muhamad Yusuf (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
The Family Hope Program is one of the program that aims to overcome public problems regarding poverity is society issued by the government which are conditionally classified as poor families in the form of social assistance as a form of social protection efforts. The purpose of this research is to study the process of evaluating the implementation of family programs in Winduaji Village, Paguyangan District, Brebes Regency. This study uses a descriptive qualitative approach that can describe problems in a study through the answers to these problems. Data collection techniques were carried out through interviews, observation and documentation. To test the validity of the data, researchers used a source triangulation technique, namely by checking the data that had been obtained through several sources. From the results of the analysis carried out on the Family Hope Program implemente, it could can run in accordaning to the regulations and procedures set by the relevant government. . This can be seen from the various activities carried out in Winduaji Village, Paguyangan District, Brebes Regency by PKH Facilitators, PKH Coordinators and community groups starting from meetings, disbursing, updating data to verifying commitments and towards the Family Hope Program. Aimed at the level of families who are slassified as poor can help meet the needs of people who are still minimal earning income in their respective families. However, there is a need for training and socialization regarding education on the use of assistance from the Family Hope program to build economic welfare independently for the people who belong to it, who in the future will not always depend on programed government assistance.